Penguatan Moderasi Beragama Melalui Implementasi Pendidikan Multikultural pada Pendidikan Sekolah Dasar - Putri, Shely Nasya; Budiman, Arif (Institut Agama Islam Sumatera Barat Pariaman, 2022)
Religious moderation is a principled attitude that it is not justified to have extreme or radical views so that it is deemed necessary to be internalized at the basic education level. This research uses a qualitative method, namely by describing the data obtained in the field and presenting it in narrative form. This research aims to provide insight into strengthening religious moderation through the implementation of multicultural education in elementary school education. As a result, multicultural education can reinforce two principles. First, the value of religious moderation which is characterized by not looking at things from one side of view, but having to find a middle point, because that is the basis for religious people in realizing harmony and comfort in relationships. Second, multicultural education plays a role in realizing citizens who shape the moral character of Indonesian society and the way society perceives a difference.